The performance of eggshell powder as an additive concrete mixed - Muhammad Nor Syafain, Hut (2014)
In this developing world, many countries are going to urbanization due to population growth. Since Malaysia is one of developing countries, the construction will grow in the future. Chicken egg is one of the waste materials which generated from the industry and it is contributed to the environmental and disposal problem due to eggshell increase continuously in recent years. Therefore, reuse eggshell as an additive in concrete is a better solution to reduce the environmental problem. The experiments were carried out into four proportions which are 0%, 5%, 10%, and 15%. These eggshells must be grinded into fine powder. The objective of the experiment is to determine the performance of eggshell powder in term of its strength. The experiments were used to investigate the eggshell is slump test, compressive strength test, flexural test and water penetration test respectively. From the results, eggshell powder in 5% additive in concrete has a good compressive strength which is 28.87.N/mm compared with the others proportion. Furthermore, it also improved in flexural strength in all additive 2 proportions. The results show eggshell powder has a best performance in water penetration test which is 11.5 mm in depth. The findings suggested that the suitability of eggshell powder with different proportions is applicable in the structural system of the buildings.